Eustrophus praecursor sp. nov.: the first Eocene species of Eustrophinae (Coleoptera: Tetratomidae) from Baltic amber - Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2022)
Based on well-preserved specimen in Baltic amber (the Kaliningrad Region, Russia), a new polypore fungus beetle of the extant Holarctic genus Eustrophus Illiger, E. praecursor sp. nov. is described and illustrated. It is the first described Cenozoic member of the subfamily Eustrophinae. This fossil record expands the diversity of Tetratomidae known to occur in the Eocene “amber forest”. A checklist of described fossil Tetratomidae is provided.